(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
ABSTRACT This study aims to determine the implementation of a website-based public information system in Taeng Village, Pallangga District, Gowa Regency. The type of research used is a qualitative research method with a descriptive type of research. The results of the study consist of six aspects, namely: 1) Communication from the transmission, clarity and consistency of communication distribution between the government and the community is still less effective. 2) Bureaucratic structure consisting of SOPs and fragmentation has been carried out in accordance with applicable regulations. 3) Resources consist of human resources, said to be ineffective because they still need staff to operate the website, the facilities and infrastructure used are adequate. 4) The disposition has been effective with the support of the village head and the community. The supporting factors are that the bureaucratic structure has been running according to the rules, the facilities and infrastructure used are adequate, and the disposition to get support from the village head and the community, the inhibiting factor is that communication has been running even though it has not been optimal, and human resources that still need additional staff. Keywords: Implementation, Information system, website